The contributions of continuing education to the pedagogical practice of literacy teachers in the time of the COVID-19 pandemic (Research, Society and Development, 2022)
This article aimed to investigate the contributions of continuing education to the pedagogical practice of literacy teachers in remote teaching situations, in the time of the Covid-19 pandemic, in the municipality of Altos-PI. The article is configured in a qualitative approach within the (auto)biographical narrative, produced from the experience of continuing education of three literacy teachers, who worked in classes of the 2nd year of the literacy cycle in the municipality of Altos-PI, which participated throughout 2020 in the online continuing training processes by Google Meet promoted by the Municipal Secretary of Education - SEMED. The methodological device used to produce the narratives was the training memorial. The study shows as a result that continuing education made possible important reflective moments, given the need to think about teaching literacy practices that could reach students in the literacy cycle in remote teaching. It also showed that other knowledge was mobilized, based on experiences, providing different forms of literacy practices, different from those traditionally used before the pandemic. It can be seen from the narratives that the teachers' inventiveness was generated due to their sensitivity, creativity and imagination in the face of challenges, leading us to understand that continuing education contributes to these innovative processes.